New prospects in the use of Kadcyla® in breast cancer - G. A. Dashyan; V. F. Semiglazov; P. V. Krivorot’ko; R. M. Paltuev; E. E. Topuzov; T. Yu. Semiglazova; E. K. Zhil’tsova; R. V. Donskikh; T. T. Tabagua; V. S. Apollonova (Опухоли женской репродуктивной системы, 2015)
As is known, the HER-2-expressing biological subtype of breast cancer (BC) is characterized by an aggressive course and has a poorprognosis in the absence of specific treatment. Before the emergence of trastuzumab, 5-year overall survival in patients with the disseminated forms of BC was 20 % (median survival, 16–29 months), out of whom only 2–5 % were long-term survivors. Addition of trastuzumab, a humanized monoclonal antibody that binds selectively to HER-2 receptor on the surface of tumor cells, to first-line chemotherapy for HER-2-positive metastatic BC caused a considerable enhancement of therapeutic efficiency. When trastuzumab is incorporated into chemotherapy for metastatic BC, median progression-free survival and overall survival were 7.4 and 25.1 months (4.6 and 20.3 months without trastuzumab), respectively. Kadcyla® (T-DM1), an antibody-drug conjugate, represents a new approach to treating HER-2-positive metastatic BC. T-DM1 is characterized by the innovative and selective mechanism of action on the HER-2-positive tumor cells. Through this mechanism, T-DM1 leads to a double antitumor effect: a trastuzumab-mediated anti-HER-2 effect and a cytotoxic effect due to the selective transport of the potent antimitotic agent DM1 into the cytoplasm. This mechanism of action enhances the efficiency of antitumor therapy and reduces toxicity. Kadcyla® has been approved in the Russian Federation, as well as by the European Medicines Agency and the United States Food and Drug Administration as monotherapy in HER-2-positive inoperable locally advanced or metastatic BC patients previously treated with taxanes and / or trastuzumab.